Manajemen Pembelajaran: Program Belajar Anak Binaan di Lapas Anak Kota Kendari - Argita Argita; Candra Gunawan; Risnawati Risnawati; Syahrini Syahrini; Nasir Nasir; Muryanto Lanontji (Journal of Education and Teaching (JET), 2021)
The purpose of this study was to analyze the assisted child learning program in Kendari City Prison. Rooted by the Law of the Republic of Indonesia in Article 31 Paragraph 1 which every citizen is obliged to attend basic education and the government is obliged to finance it. The research method uses a qualitative approach. This qualitative data is obtained by making direct observations, with the aim of obtaining an overview of the implementation of child development activities in prisons. Meanwhile, observation and document analysis are used to validate data from interviews. The results showed that the education process in LPKA was carried out in accordance with the LPKA guidebook which was classified according to the law decided by the judge. Due to limited facilities and infrastructure, the education planning process in LPKA still uses minimal facilities, although not maximally. Even so, the assisted children can still experience education and experience many changes in both behavior and morals.